Synthesis, electrochemical and spectroelectrochemical properties of peripherally tetra-imidazole substituted metal free and metallophthalocyanines - KOCA, ATIF (ELSEVIER SCI LTD, 2013)
The synthesis and characterization of novel organosoluble peripherally tetra imidazole substituted metal-free (4), zinc(II) (5), nickel(II) (6), cobalt(II) (7), lead(II) (8) and oxo-titanium(IV) (9) phthalocyanines are described for the first time in this study. Electrochemical and spectroelectrochemical measurements exhibit that while copper phthalocyanine gives only ring-based electron transfer reactions, incorporating redox active metal centers, Co(II), and Ti(IV)OPc, into the phthalocyanine core extends the redox richness of the phthalocyanine ring with the metal-based reduction and oxidation couples of the metal centers in addition to the common phthalocyanine ring-based electron transfer processes. In-situ electrocolorimetric measurements of the complexes allow quantification of color coordinates of the each electrogenerated anionic and cationic redox species. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Synthesis; Phthalocyanine; Imidazole; Electrochemistry; Spectroelectrochemistry; Soluble; IN-SITU; ELECTROCATALYTIC ACTIVITY; HYDROGEN-PRODUCTION; CARBON-DIOXIDE; THIN-FILMS; PHTHALOCYANINES; COBALT; MANGANESE; COMPLEXES; REDUCTION